'I couldn't hold the whole thing': the role of gender, individualisation and risk in shaping fertility preferences in Taiwan. Issue 1 (2nd January 2018) - Freeman, Emily; Xiaohong, Ma; Ping, Yan; Wenshan, Yang; Gietel-Basten, Stuart
ABSTRACT: Taiwan has one of the lowest fertility rates in Asia. High direct and indirect costs of childbearing have been identified as key drivers behind this at the macro-level, but little is known about the mechanism of these influences at the individual-level. In 32 qualitative interviews with parents in Taipei, we sought to explore the salient factors for couples in their decisions about having further children. We identified a tension between gendered expectations of childcare responsibilities and women's desire to 'build a life of one's own' – a life with options and the freedom to pursue career and social aspirations. Based on our grounded analysis, we reflect on the high relevance of individualisation, risk society and incomplete gender revolution theories for understanding why many couples – and women in particular – choose to cease childbearing at parity one.